2006
DOI: 10.1093/hmg/ddl008
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between FOXC1 and PITX2 underlie the sensitivity to FOXC1 gene dose in Axenfeld–Rieger syndrome and anterior segment dysgenesis

Abstract: Axenfeld-Rieger ocular dysgenesis is associated with mutations of the human PITX2 and FOXC1 genes, which encode transcription factors of the homeodomain and forkhead types, respectively. We have identified a functional link between FOXC1 and PITX2 which we propose underpins the similar Axenfeld-Rieger phenotype caused by mutations of these genes. FOXC1 and PITX2A physically interact, and this interaction requires crucial functional domains on both proteins: the C-terminal activation domain of FOXC1 and the hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 37 publications
4
121
0
1
Order By: Relevance
“…Enhanced FOXC1 SUMOylation could therefore make individuals more susceptible to developing diseases associated with the syndrome, whereas loss of SUMOylation could attenuate the effects of the mutation. Similarly, chromosomal duplications increasing FoxC1 gene dosage lead to significant anterior segment defects (51), and elevated FOXC1 activity gives rise to ocular abnormalities similar to loss of PitX2, which is a negative regulator of FOXC1 (52). Thus, loss of FOXC1 SUMO modification either through mutations in FOXC1 or through alterations in the factors and signals controlling it could be associated with such developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced FOXC1 SUMOylation could therefore make individuals more susceptible to developing diseases associated with the syndrome, whereas loss of SUMOylation could attenuate the effects of the mutation. Similarly, chromosomal duplications increasing FoxC1 gene dosage lead to significant anterior segment defects (51), and elevated FOXC1 activity gives rise to ocular abnormalities similar to loss of PitX2, which is a negative regulator of FOXC1 (52). Thus, loss of FOXC1 SUMO modification either through mutations in FOXC1 or through alterations in the factors and signals controlling it could be associated with such developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing mouse eye, Pitx2 and Foxc1 are co-localized in periocular mesenchyme and they interact physically through crucial functional domains. 20 Furthermore, PITX2 can act as a negative regulator of FOXC1 activity, by binding to FOXC1 and repressing activation of putative FOXC1 target genes. 20 This interaction has importance in understanding the effects of the different mutations of these genes as explained below.…”
Section: Pitx2 and Foxc1mentioning
confidence: 99%
“…Furthermore, several studies have shown that duplication of FOXC1 may also lead to ARS phenotype. Berry et al 20 have shown that FOXC1 transcriptional activity was negatively regulated by PITX2 and this explains how contrasting mutations (duplication of FOXC1 and deletion of PITX2) lead to similar phenotypes: PITX2 binds to FOXC1 and this represses activation of putative FOXC1 target genes. When PITX2 is mutated, the FOXC1 target genes are activated leading to ARS.…”
Section: Foxc1 Defects and Arsmentioning
confidence: 99%
“…21 PITX2 can inhibit the transactivation activity of FOXC1, which is lost in the presence of PITX2 loss-of-function variants. 21 The transcriptional activity of both genes requires tight regulation during embryogenesis for proper development of anterior segment tissues.…”
Section: Introductionmentioning
confidence: 99%